Notary's Accountability for Non-Compliance with Covernote Issuance in Corruption Cases - Raisyha Talitha; Taupiqqurrahman (Magister Ilmu Hukum Fakultas Hukum Universitas Riau, 2025)
The absence of specific legal provisions regarding the issuance of covernotes in Indonesia has created legal uncertainty and opened opportunities for misuse of notarial authority in issuing covernotes. This study aims to examine the authority of notaries in issuing covernotes based on the attributive authority granted by the state as stipulated in Article 16 paragraph 1 letter a of the Notary Law (UUJN), as well as to analyze the forms of notary liability concerning the irregularities in the issuance of covernotes in a corruption case under Decision Number 51/Pid.Sus-TPK/2022/Pn.Pbr. The results of the study indicate that the authority of notaries in issuing covernotes is still based on customary practice (living law) in the law of obligations and lacks a strong legal foundation. The liability that may be imposed on notaries for covernote irregularities can take the form of criminal, civil, and administrative liability. This research is expected to contribute by proposing a revision of the Notary Law (UUJN) to include specific provisions on covernotes and to clarify the mechanism of notary liability in issuing covernotes. Thus, it is expected that the legal regulation of covernotes will become more transparent and emphasize the principle of accountability.